Profile of self-adjustment and level of academic stress during online learning in higher education - Azmiyyah, Husnul; Lianawati, Ayong (ProGCouns: Journal of Professionals in Guidance and Counseling, 2021)
This study aims at determining the profile of self-adjustment and academic stress levels during the online learning period of students at Faculty of Engineering PGRI Adi Buana University, Surabaya. The method used was survey quantitative research. The sampling technique used was a saturated sample for a more accurate representation. There were 200 students of total from department of industry, electrical, environment, urban planning, fashion, make-up, and gastronomy. The data collection techniques used were two questionnaires, namely self-adjustment and academic stress which were collected through online application. The data analysis technique used in this research was descriptive statistics. The results show that the self-adjustment of engineering faculty students was in the poor and high category. The adjustment aspect in the low category was found in the aspect of expressing feelings for 62%, while the academic stress in the high category was found in the aspect of change for 78%. It can be concluded that most of research participants during the online learning were still in a stable condition. However, there were several percentages of aspects that were less than perfect in the process of either self-adjustment or the level of academic stress.